The Influence of Social Media on Political Participation in the Digital Era - Teguh Supriyanto (Austronesia Akademika, 2024)
Social media has become a dominant platform in political communication in the digital era. This article explores the influence of social media on political participation, particularly in the context of Indonesia. Using a qualitative descriptive research method, this study reveals that social media not only enhances access to political information but also strengthens citizens' engagement in the political process. However, challenges such as the spread of misinformation and political polarization also arise. This analysis provides essential insights for developing more inclusive and effective political participation strategies in the digital era. In the digital era, social media has emerged as a dominant platform for political communication, reshaping how individuals participate in the political process. This article examines the influence of social media on political participation, with a specific focus on the Indonesian context. Through a qualitative descriptive research approach, the study highlights how social media not only expands access to political information but also fosters greater civic engagement. However, it also addresses the challenges posed by misinformation and political polarization. The findings offer critical insights into developing more inclusive and effective strategies for political participation in the digital age.